Disparities in program enrollment and employment outcomes for veterans with psychiatric and co-occurring substance use disorders referred or enrolled for VHA vocational rehabilitation - Sprong, Matthew E.; Hollender, Heaven; Lee, Yu-Sheng; Rawlins Williams, Lee Ann; Sneed, Zach; Garakani, Amir; Buono, Frank D. (Frontiers in Psychiatry, 2023)
Introduction The purpose of the study was to investigate factors that influence vocational rehabilitation program enrollment and employment at discharge of veterans with psychiatric and co-occurring alcohol and other substance use disorders enrolled at a veteran health administration (VHA) medical center. Methods A sample of 2,550 veteran patients referred for VHA vocational rehabilitation between 2016 and 2021 were examined for the current study. The current study was classified as quality improvement/assurance, thus resulting in exempt research by the U.S. Department of Veteran Affairs Institutional Review Board. Results Veterans with active alcohol use disorders (AUDs) and co-occurring depression, anxiety, post-traumatic stress disorder, or bipolar disorders were less likely to be enrolled for vocational rehabilitation program services compared to those without these co-occurring diagnoses. Veterans with AUD (active & in-remission status combined into one category) and a diagnosis of anxiety were less likely to be employed at discharge compared to veterans with AUDs and no anxiety diagnosis (anxiety diagnosis – 3.5% vs. no anxiety diagnosis – 5.8%). Discussion VHA vocational rehabilitation can be an effective intervention to assist veterans in reintegrating back into the community. Yet, there appears to be some disparities in the program enrollment and employment at discharge, depending on the nature of the psychiatric diagnosis. Investigating the factors contributing (mediating or moderating) to these discrepancies are needed. Although it appears access is not the issue in being referred for vocational rehabilitation services, other factors are likely contributing to program entry.